Pungutan Biaya Pariwisata Pantai Selatan Kabupaten Bantul Berdasarkan Peraturan Bupati (PERBUP) Kabupaten Bantul Nomor 106 Tahun 2022 - R Priyo Yuli Nurcahyo; Syukron Abdul Kadir; Jumadi (CV. Multi Kreasi Media, 2023)
This study reviews the levy of tourism fees for the south coast of Bantul Regency Number 106 of 2022 which aims to ensure that local original income from the tourism sector increases fairly and in accordance with applicable regulations so as to avoid illegal levies carried out by irresponsible individuals. This research uses a qualitative approach with a type of literature study research. Data in this study was obtained from reviewing various books, journals, laws and other documents that can support the results of this study. The results of this study show that the contribution of tourism in Bantul Regency has a significant influence on regional income through the withdrawal of levies from tourist visitors. Local governments have regulated regulations related to the withdrawal of tourism levies, including levy rates, as well as procedures for collecting and paying levies. The establishment of policies related to tourism levies aims to ensure that local original revenues from the tourism sector increase fairly and in accordance with applicable regulations.